Pore size and LbL chitosan coating influence mesenchymal stem cell in vitro fibrosis and biomineralization in 3D porous poly(epsilon‐caprolactone) scaffolds. Issue 7 (29th December 2014) - Mehr, Nima Ghavidel; Li, Xian; Chen, Gaoping; Favis, Basil D.; Hoemann, Caroline D.
Abstract: Poly(epsilon‐caprolactone) (PCL) is a hydrophobic bioplastic under development for bone tissue engineering applications. Limited information is available on the role of internal geometry and cell‐surface attachment on osseous integration potential. We tested the hypothesis that human bone marrow mesenchymal stem cells (MSCs) deposit more mineral inside porous 3D PCL scaffolds with fully interconnected 84 or 141 µm pores, when the surfaces are coated with chitosan via Layer‐by‐Layer (LbL)‐deposited polyelectrolytes. Freshly trypsinized MSCs were seeded on PCL 3D cylinders using a novel static cold seeding method in 2% serum to optimally populate all depths of the scaffold discs, followed by 10 days of culture in proliferation medium and 21 additional days in osteogenic medium. MSCs were observed by SEM and histology to spread faster and to proliferate more on chitosan‐coated pore surfaces. Most pores, with or without chitosan, became filled by collagen networks sparsely populated with fibroblast‐like cells. After 21 days of culture in osteogenic medium, sporadic matrix mineralization was detected histologically and by micro‐CT in highly cellular surface layers that enveloped all scaffolds and in cell aggregates in 141 µm pores near the edges. LbL‐chitosan promoted punctate mineral deposition on the surfaces of 84 µm pores ( p < 0.05 vs. PCL‐only) but not the 141 µm pores. This study revealed that LbL‐chitosan coatings are sufficient to promote MSC attachment to PCL but only enhance mineral formation in 84 µm pores, suggesting a potential inhibitory role for MSC‐derived fibroblasts in osteoblast terminal differentiation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2449–2459, 2015.